Anaplastic thyroid carcinoma with chondrosarcomatous differentiation: a case report - Jixuan Liu; Ni Cui; Wenjia Ding; Xinjie Dong; Xiaoshuai Chen; Jun Jiang; Yafang Liu (BMC, 2020)
Abstract Background Anaplastic thyroid carcinoma (ATC) is a rare malignant tumor. In addition to the main ATC type with classical histopathological features, the other morphological types of ATC include paucicellular variant, angiomatoid, lymphoepithelioma-like, and small-cell variant. However, an ATC variant with a chondrosarcomatous component has not been reported to date. Case presentation Computed tomography imaging of a 63-year-old male with a 2-month history of a cervical mass revealed a 4.5-cm lesion with heterogeneous enhancement in the left thyroid lobe and two smooth and homogeneous nodules in the right thyroid lobe. The patient underwent total thyroidectomy and cervical lymph node resection. Histologically, the tumor boundary in the left lobe was clear, with a few mitotically active, spindle sarcoma-like tumor cells observed in some areas. Immunohistochemically, these spindle cells were positive for vimentin and negative for cytokeratin, paired box-8, epithelial membrane antigen, calcitonin, thyroglobulin, and thyroid transcription factor-1. In other areas, abundant cartilage matrix production and irregularly shaped lobules of cartilage, often separated by fibrous bands, were observed. The chondrocytes appeared mildly/moderately atypical and contained enlarged, hyperchromatic nucleoli. One of the two nodules in the right thyroid lobe had a clear boundary and comprised some bland spindle cells in a prominently collagenous stroma with clear boundaries. The other nodule in the right thyroid lobe was completely enclosed within a thin, fibrous capsule and exhibited normofollicular and microfollicular architecture. The patient received adjuvant radiotherapy after the surgery and was free of any local or regional recurrence or distant metastases at the 8-month follow-up evaluation. Conclusions This unusual case of ATC with chondrosarcomatous differentiation is an important addition to the morphology spectrum of ATC types.